Summary of research progress on industrial flue gas desulfurization technology - Li, Xueke; Han, Jinru; Liu, Yan; Dou, Zhihe; Zhang, Ting-an (Separation and purification technology, 2022)
•The ultra-low emission purification technologies of SO2 in flue gas are described.•The advantages and disadvantages of several desulfurization methods are compared.•The research status of desulfurization technology is described.•The mass transfer mechanisms of several desulfurization technologies are reviewed.•The current development problems and future research directions of desulfurization technology are pointed out. Through the purification technology of flue gas desulfurization, ultralow emissions of SO2 flue gas in industrial flue gas can be achieved. This article involves dry desulfurization, semi-dry desulfurization, and wet desulfurization technologies. The research progress of these technologies since they were first proposed is summarized, and the problems existing in these desulfurization technologies are analyzed. The theory of mass transfer and absorption in flue gas desulfurization is summarized, and the optimal desulfurization process parameters for the operation of desulfurization technology are obtained. A high added value production of desulfurization technology can be realized by studying the recycling of desulfurization products. This paper summarizes the characteristics and the latest research progress of various desulfurization technologies, and aims to provide help for the better development of desulfurization technologies. It also provides suggestions for the future research direction of desulfurization technology.